If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 8) + (-2x + 7) = 0 Reorder the terms: (8 + 3x) + (-2x + 7) = 0 Remove parenthesis around (8 + 3x) 8 + 3x + (-2x + 7) = 0 Reorder the terms: 8 + 3x + (7 + -2x) = 0 Remove parenthesis around (7 + -2x) 8 + 3x + 7 + -2x = 0 Reorder the terms: 8 + 7 + 3x + -2x = 0 Combine like terms: 8 + 7 = 15 15 + 3x + -2x = 0 Combine like terms: 3x + -2x = 1x 15 + 1x = 0 Solving 15 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 1x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + 1x = 0 + -15 1x = 0 + -15 Combine like terms: 0 + -15 = -15 1x = -15 Divide each side by '1'. x = -15 Simplifying x = -15
| x^5+3x^3+72=0 | | -12-5x(6-2m)=18 | | -7b-7a=12 | | 6x+8=-2x+32 | | 12-y=15 | | 20+2(y+41)=38 | | 25=x+y | | 6x-0.8x^2=0 | | 6.1(3.1+2.5)=15.3x-3.9 | | 3(31-12c)=82 | | 2(y-5)=24 | | 29y-50=24 | | 0=4-(4*1*c) | | 18-x=13 | | e+e+e+e+e=45 | | y=sin(x)cos(sin(x)) | | -37=P-18 | | -4X-5(8-4X)=15+5X | | x^2-2x+c=0 | | 6-x=11-3x | | 7(-2-3X)=91 | | y=5x^4 | | 3-6y=8 | | 3g+4=19 | | 3g+4= | | 5-4x=3+x | | 3x^2=10-2x | | 3x+4+3x-2=42 | | -7(1-4v)-8v=-167 | | 3y+5+2y+1=31 | | -3-5(3-6r)=-258 | | 2=8+4a |